Efflux-Mediated Resistance to Tigecycline (GAR-936) in Pseudomonas aeruginosa PAO1 - Dean, Charles R. (American Society for Microbiology, 2003)
Pseudomonas aeruginosa strains are less susceptible to tigecycline (previously GAR-936; MIC, 8 μg/ml) than many other bacteria (P. J. Petersen, N. V. Jacobus, W. J. Weiss, P. E. Sum, and R. T. Testa, Antimicrob. Agents Chemother. 43:738-744, 1999). To elucidate the mechanism of resistance to tigecycline, P. aeruginosa PAO1 strains defective in the MexAB-OprM and/or MexXY (OprM) efflux pumps were tested for susceptibility to tigecycline. Increased susceptibility to tigecycline (MIC, 0.5 to 1 μg/ml) was specifically associated with loss of MexXY. Transcription of mexX and mexY was also responsive to exposure of cells to tigecycline. To test for the emergence of compensatory efflux pumps in the absence of MexXY-OprM, mutants lacking MexXY-OprM were plated on medium containing tigecycline at 4 or 6 μg/ml. Resistant mutants were readily recovered, and these also had decreased susceptibility to several other antibiotics, suggesting efflux pump recruitment. One representative carbenicillin-resistant strain overexpressed OprM, the outer membrane channel component of the MexAB-OprM efflux pump. The mexAB-oprM repressor gene, mexR, from this strain contained a 15-bp in-frame deletion. Two representative chloramphenicol-resistant strains showed expression of an outer membrane protein slightly larger than OprM. The mexCD-OprJ repressor gene, nfxB, from these mutants contained a 327-bp in-frame deletion and an IS element insertion, respectively. Together, these data indicated drug efflux mediated by MexCD-OprJ. The MICs of the narrower-spectrum semisynthetic tetracyclines doxycycline and minocycline increased more substantially than did those of tigecycline and other glycylcyclines against the MexAB-OprM- and MexCD-OprJ-overexpressing mutant strains. This suggests that glycylcyclines, although they are subject to efflux from P. aeruginosa, are generally inferior substrates for P. aeruginosa efflux pumps than are narrower-spectrum tetracyclines.